Evaluation of primary surgical outcomes in New Zealand patients with unilateral clefts of the lip and palate - Jack Hannah C.; Antoun Joseph S.; Fowler Peter V. (Sciendo, 2011)
Objective: To evaluate and compare the primary surgical outcomes of complete unilateral cleft lip and palate (UCLP) patients in two New Zealand cleft care centres.